Testing the Role of Authenticity in Cultural Tourism Consumption: A Case of Mauritius - Ramkissoon, Haywantee; Uysal, M. (Croatian National Tourist Board, 2010)
Tourists’ interests in traveling to natural and cultural heritage sites of different destinations in the quest for authenticity have fueled the growth of the cultural tourism industry in such economies. The purpose of the present study is to broaden the understanding of authenticity’s various interpretations in the cultural tourism consumption context. Data were collected at 10 selected cultural and natural heritage sites in the island of Mauritius. Structural equation modeling was employed on a total sample of 600 tourists after a pretest. Path analysis was used to examine the effect of felt authenticity on tourists’ intentions to consume cultural heritage attractions. Results indicated that the issue of authenticity is fundamental in destinations hosting unique natural and cultural resources increasingly sought by the modern traveler. The study enriches the theoretical and practical contributions of felt authenticity as a determinant of tourists’ intentions to consume cultural authenticity in small island destinations.